Overview of power exhaust experiments in the COMPASS divertor with liquid metals. (December 2020) - Dejarnac, R.; Horacek, J.; Hron, M.; Jerab, M.; Adamek, J.; Atikukke, S.; Barton, P.; Cavalier, J.; Cecrdle, J.; Dimitrova, M.; Gauthier, E.; Iafrati, M.; et al.
Highlights: Power exhaust of a CPS liquid metal divertor target in ELMy conditions is reported. Good power handling of Li and LiSn up to ~12 MW/m 2 and ELM energy fluence 15 kJ/m 2 . No droplets directly ejected from the CPS mesh and no damage of the latter observed. No contamination of the core and SOL plasmas by tin was observed. Neutral Li is very well localized in the close vicinity of the CPS mesh. Abstract: Power handling experiments with a special liquid metal divertor module based on the capillary porous system technology were performed in the tokamak COMPASS. The performance of two metals (Li and LiSn alloy) were tested for the first time in a divertor under ELMy H-mode conditions. No damage of the capillary mesh and a good exhaust capability were observed for both metals in two separate experiments with up to 12 MW/m 2 of deposited perpendicular, inter-ELM steady-state heat flux and with ELMs of relative energy ~3% and a local peak energy fluence at the module ~15 kJ.m −2 . No droplets were directly ejected from the mesh top surface and for the LiSn experiment, no contamination of the core and SOL plasmas by Sn was observed. The elemental depth profile analysis of 14 stainless-steel samples located around the vacuum vessel for each experiment provides information about the migration of evaporated/redeposited liquid elements.